Improvement of resistance-spot-welded joints for DP 600 steel and A5052 aluminum alloy with Zn slice interlayer. (December 2017) - Chen, Jianbin; Yuan, Xinjian; Hu, Zhan; Li, Ting; Wu, Kanglong; Li, Ci
Graphical abstract: Highlights: A5052 and DP 600 with Zn interlayer were investigated by resistance spot welding. Tensile-shear strength of the welded spot increased pronouncedly. Plug failure mode was present during mechanical property testing. Microstructure of the welded spot, especially interface region, was improved markedly. EBSD, TEM and SEM were employed to investigate the joint microstructure. Abstract: The microstructure and mechanical properties of resistance spot welded DP 600 advanced high strength steel and A5052 aluminum alloy joint were improved with 50 μm Zn slice interlayer. The results showed that the fusion zone (FZ) grain of A5052 was columnar crystal with rough pattern. The microstructure of FZ and the heat affected zone (HAZ) for DP 600 were coarse-lath martensite and ferrite-fine martensite, respectively. The intermetallic compound (IMC) in the interface region included Fe2 Al5, Fe4 Al13 and Fe11 Zn40 . The main IMC was present in winding pattern, which could be responsible for the improvement of mechanical properties. The tensile-shear load reached to a maximum value (7.06 kN), increased by 28% as compared to the case without Zn slice interlayer. The obvious plastic deformation took place prior to fracture, and the fracture exhibited plug failure (PF) mode rather than interfacial failure (IF) mode. Many dimples were found on the fracture surface.